Inventories and the Business Cycle - Barber, Clarence L. (Book collections on Project MUSE., 1958)
This study falls into two parts. Part I contains a theoretical analysis of the relation of inventories and inventory fluctuations to the business cycle. It begins with a brief survey of the treatment of inventories in the literature of business cycles. Then a theoretical model of the economic system is developed as a basis for judging the nature and importance of inventory fluctuations in the economy. Part II is a study of inventory fluctuations in Canada over the period from 1918 to 1950 and provides some inductive verification of the preceding theoretical argument. The behaviour of inventories in ten important manufacturing industries is analysed in detail. This part also contains analysis of the movement of total inventories and of the behaviour of inventories in the main industrial subdivisions of the economy. Finally a brief chapter relates these findings to the theoretical analysis of Part I. Canadian Studies in Economics, No. 10.